622.DRYING CONDITIONS FOR PADDY PROCESSING IN MIXED-FLOW HIGH-CAPACITY PLANT - Filip Mojsovski (MECHANICAL ENGINEERING – SCIENTIFIC JOURNAL, 2020)
A research was conducted to obtain information on needed procedures for transforming one universal cereal dryer in special equipment for paddy. Harvested paddy was dried under controlled air conditions in continuous-flow high-capacity grain dryer. The realization of the planned study was carried out in three steps: 1) correction of dryer construction, 2) insertion of intermittent drying process, and 3) selection of correct drying conditions. Intermittent drying process was studied by tempering paddy during its processing. In a drying section two zones system was exploited, zone 1 with air temperatures up to 45oC, and zone 2 with air temperatures up to 40 oC. In a cooling section air temperatures up to 26 oC were used. Variations in moisture content, between the grains from two successive horizontal elements of the dryer, were in the range of near one percentage points. In the first horizontal elements of heating section, the variation of moisture content wet basis was two times higher than in the rest horizontal elements of drying section. Correct drying conditions, for local paddy varieties, were selected and are reported.